Pengaruh tingkat suku bunga, inflasi, dan non performing loan terhadap pemberian kredit dan dampaknya terhadap kinerja keuangan - Jufriadi, Jufriadi; Imaduddin, Imaduddin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of interest rates, inflation, and non-performing loans on lending and their impact on the financial performance of banking companies listed on the IDX. The population of this study were all banks listed on the Indonesia Stock Exchange for the period 2013-2015, totaling 43 banks. Sample selection through purposive sampling method. There are 21 companies that meet the criteria as the research sample so that the research data is 63. The data analysis technique used is the classical assumption test and hypothesis testing. The results of this study indicate that the interest rate has a significant and negative effect on lending. Inflation partially has a negative and significant effect on lending. Non-Performing Loan partially has a negative and significant effect on lending. The partial distribution of credit has a positive and significant effect on financial performance. The interest rate has a positive and significant effect on the company's performance as proxied by ROA. Inflation partially has a positive and significant effect on financial performance. Non-Performing Loans have a negative and significant effect on the financial performance of banks